Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Badan Keuangan Kabupaten Lima Puluh Kota: Indonesia - Hariman Syaleh; Rohimah Nur Nasution (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effect of work discipline and work motivation on the performance of civil servants at the Financial Agency of Fifty Cities Regency. Here the author describes the influence of work discipline and work motivation on performance. The total population in this study were 72 people as well as samples in this study. Data were collected through the distribution of a questionnaire with a Likert scale model and then tested for the validity and reliability of the questionnaire. The data analysis technique used is the multiple linear regression method using the SPSS 23.00 program. The purpose of multiple linear regression is to see the relationship between the influence of the independent variable on the dependent variable. The results of this study are a). Work discipline (X1) has a positive and significant influence on the performance of civil servants at the Fifty Cities District Finance Agency. b). Work motivation (X2) has a positive and significant influence on the performance of civil servants at the Fifty Cities District Finance Agency. c). Work discipline and work motivation together have a significant positive effect on the Performance of Civil Servants at the Financial Agency of Fifty Cities Regency. Keywords: Discipline, Motivation and Performance